2018
DOI: 10.1093/ckj/sfy096
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of renal involvement in cryoglobulinaemia: a retrospective study of 153 patients

Abstract: Background The course of cryoglobulinaemia varies widely, from asymptomatic patients to severe vasculitis syndrome. Renal involvement (RI) is the major prognostic factor, and frequently occurs several years after diagnosis. However, predictive factors for RI are not well known. The aim of our study was to identify RI predictive factors during cryoglobulinaemia. Methods We retrospectively reviewed the clinical charts of a consecutive series of 153 patients positive for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…This may be the reason for the high prevalence of renal involvement. A retrospective study of 153 French patients, in which 45 patients had renal involvement, showed that type II cryoglobulinemia, a high serum cryoglobulin concentration, the presence of an IgG kappa monoclonal component, and diabetes were independently associated with the risk of renal involvement, and no particular etiology independently predicted renal involvement (13). In our cohort, we found no differences in clinical manifestations among the three groups of patients based on secondary causes.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This may be the reason for the high prevalence of renal involvement. A retrospective study of 153 French patients, in which 45 patients had renal involvement, showed that type II cryoglobulinemia, a high serum cryoglobulin concentration, the presence of an IgG kappa monoclonal component, and diabetes were independently associated with the risk of renal involvement, and no particular etiology independently predicted renal involvement (13). In our cohort, we found no differences in clinical manifestations among the three groups of patients based on secondary causes.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies have shown that the most common renal pathology pattern in patients with cryoglobulinemia was MPGN, and other studies have reported mesangial proliferative glomerulonephritis (MsPGN), MN, FSGS, fibrillary or immunotactoid glomerulopathy, and thrombotic microangiopathy (TMA) ( 14 , 15 ). In a French cohort, 14 patients underwent renal biopsy, the majority of whom had MPGN (13/14) ( 13 ). Here in our study, MPGN was the most common renal pathology pattern, followed by lupus nephritis, MN, and RPGN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mouse models cannot be transferred to humans, because mouse IgG1 resembles human IgG4, not involved in type I CG pathophysiology. The involvement of one specific IgG subclass in renal manifestations in humans is not clear because renal manifestations appear several years after CG diagnosis [29]. This delay could explain differences in the reported results and justify a long follow-up study of patients.…”
Section: Igg Subclasses and Clinical Manifestations Of Type I Cgmentioning
confidence: 92%
“…As the disease progresses, severe irreversible clinical manifestations such as glomerulonephritis, peripheral neuropathy, and skin ulcers occur, and the 10-year survival rate was significantly reduced. At the same time, patients with MC have poor response to treatment, high mortality rate and sequelae rate of chronic organ failure (such as chronic renal failure and lymphoma) [4,5] . Therefore, cryoglobulinemia is a disease with atypical symptoms and serious injury to patients.…”
mentioning
confidence: 99%